1995
DOI: 10.1017/s1047951100002778
|View full text |Cite
|
Sign up to set email alerts
|

Normal values for cardiac and great arterial dimensions in premature infants by cross-sectional echocardiography

Abstract: The number of neonates who undergo intracardiac repair for congenital heart disease has increased in recent years. In considering appropriate surgical options in such circumstances, normal values for various cardiovascular dimensions are needed. We measured 19 parameters for the heart and great arteries (four valves, pulmonary tree, aortic arch, ascending and descending aorta, ventricular septum, left ventricular internal and posterior wall dimensions) using cross-sectional echocardiography in 55 premature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Imai et al 7 reported that the increase in the rate of development of left ventricular end-diastolic dimension correlated closely with body weight in 55 premature and full-term infants, with weight ranging from 543 to 3966 grams. They reported the equation as left ventricular end-diastolic dimension = 9.369 + 2.161 × (body weight in kilogram) and r-value as 0.74.…”
Section: Discussionmentioning
confidence: 99%
“…Imai et al 7 reported that the increase in the rate of development of left ventricular end-diastolic dimension correlated closely with body weight in 55 premature and full-term infants, with weight ranging from 543 to 3966 grams. They reported the equation as left ventricular end-diastolic dimension = 9.369 + 2.161 × (body weight in kilogram) and r-value as 0.74.…”
Section: Discussionmentioning
confidence: 99%
“…In 1995, Imai et al [26] measured 19 parameters for the heart and great artery (four valves, pulmonary tree, aortic arch, ascending and descending aorta, ventricular septum, and left ventricular internal and posterior wall dimensions) using cross-sectional echocardiography in 55 premature and full-term infants (ranging in gestational age from 23 weeks to 41 weeks, and in body weight from 543 g to 3966 g). The increase in each dimension correlated closely with body weight and was found to follow a linear regression.…”
Section: Discussionmentioning
confidence: 99%